Voting the gender gap - Whitaker, Lois Duke (University of Illinois Press, 2008)
This book concentrates on the gender gap in voting--the difference in the proportion of women and men voting for the same candidate. Evident in every presidential election since 1980, this polling phenomenon reached a high of 11 percentage points in the 1996 election. The contributors discuss the history, complexity, and ways of analyzing the gender gap; the gender gap in relation to partisanship; motherhood, ethnicity, and the impact of parental status on the gender gap; and the gender gap in races involving female candidates. Voting the Gender Gap analyzes trends in voting while probing how women's political empowerment and gender affect American politics and the electoral process. _x000B__x000B_Contributors are Susan J. Carroll, Erin Cassese, Cal Clark, Janet M. Clark, M. Margaret Conway, Kathleen A. Dolan, Laurel Elder, Kathleen A. Frankovic, Steven Greene, Leonie Huddy, Mary-Kate Lizotte, Barbara Norrander, Margie Omero, and Lois Duke Whitaker._x000B_